Promotion of Au nanoparticles on carbon frameworks for alkali-free aerobic oxidation of benzyl alcohol - Du, Zhongtian; Zhang, Sen; Yang, Sihan; Yang, Wenhao; Luo, Jingjie; Liang, Changhai (Frontiers in Chemical Engineering, 2023)
In a recent work, we have synthesized a series of modified Co-ZIF-67 materials with tunable morphology to support fine Au nanoparticles for the alkali-free aerobic oxidation of benzyl alcohol. The structure promotion was operated using Stöber silica as hard template and subsequently removed by NaOH etching before gold immobilization. The texture structure of Au/(Si)C was greatly improved with increasing surface area and volume. CoOx was simultaneously introduced into the carbon shell originated from the Co-ZIF-67 precursor, which consequently facilitated the specific Au-support interaction via bimetallic synergy. The redispersion of both Au and CoOx as well as the electronic delivery between metals were evidenced by XRD, XPS and TEM images. The analysis on the chemical and surface composition suggested the surface rich Auδ+ with abundant lattice oxygen contributed by CoOx in the final Au/(Si)C, which reasonably benefited the transformation rate of benzyl alcohol even in an alkali-free condition. Using the Au/(Si)C with finely dispersed Au particles, a nice catalytic performance in the alkali-free environment was reached with 89.3% benzyl conversion and 74.5% benzaldehyde yield under very mild condition.